Physicians’ attitude towards Cancer and Cancer Patients in Jose R Reyes Memorial Medical Center - Shrestha, Deepak Sundar; Manandhar, Sajani; Rijal, Rajendra; Ngelangel, Corazon A (Asian Pacific Journal of Cancer Care, 2021)
Introduction: This study evaluates the attitude of physicians regarding cancer the disease and patients with cancer, which may influence their management allowing for recommendations of appropriate interventions. Methods: This is a cross-sectional study, which interviewed 251 physicians of Jose R Reyes Memorial Medical Center regarding their attitudes on cancer and cancer patients. The study also explored and identified factors associated with such attitudes. The validated modified Cancer Attitude Scale of Haley et al (1968, 1977) was used. Ordinal (proportional odds) regression via Stata was used to examine the association between independent and dependent variables. A score of 1 to 5 was given from strongly agree to strongly disagree for all 21 negatively affirmed questions and a score of 1 to 5 was given from strongly disagree to strongly agree for the 11 positively affirmed questions. The cut off levels to say positive or negative attitude was set as a median score of above 3 for each question representing positive attitude and score of below 3 representing negative attitude. Results: In general the overall attitude of physicians working in Jose R Reyes Memorial Medical Center towards cancer and cancer patients is positive. However the physicians are skeptical of the patient’s inner resource to cope with cancer. Expertise, years of practice (of more than 25 years), having experience with cancer patients, being active in religion, Filipino nationality and protecting oneself from carcinogens showed to be associated with positive attitude. Conclusion: The factors that affect physicians’ attitude towards cancer and cancer patients should be further explored with a larger and more representative population of physicians for a wider view of attitudes across age groups, clinical experience, religion, medical specialty among others; so that appropriate interventions may be devised to determine ways that can positively impact their perception. Hence, improving patient management.